The Role Mediation of Export And Foreign Debt in Influences Exchanges Rate on Foreign Exchange Reserves: Evidence from Indonesian - Manat Rahim; Muhamad Armawaddin; Ahmad Ahmad (Universitas Negeri Malang, 2019)
The purpose of this study is to examine and analyze the role of export and foreign debt mediation in the effect of exchange rate on foreign exchange reserves. And test and analyze the effect of exchange rate on exports, foreign debt and foreign exchange reserves and the effect of exports and foreign debt on foreign exchange reserves in Indonesian in 1999-2015. The type of research data is secondary data sourced from Bank Indonesian and Central Bureau of Statistics. Data analysis with path analysis using AMOS 18.0.The results of the analysis and discussion concluded that in the period of 1999-2015, export and foreign debt play a role mediate the effect of exchange rate on foreign exchange reserves in Indonesia. The significance test results conclude that the effect mediation of export and foreign debt is significant on foreign exchange reserves. Other results conclude that exchange rate has significant effect on export, foreign debt and foreign exchange reserves. Export and foreign debt have a significant effect on foreign exchange reserves in Indonesian.